INTEGRASI SENSORI MELALUI BRAIN-GYM DENGAN LAGU DAERAH DI SPS ASTER 131 JEMBER - Alifia Tittandi, Nindya; Buroidah, Hikmah; Dwi Afifah, Dinda; Salsabila, Aasyah; Endarwati, Kasihani (Jurnal Pengabdian Pendidikan Masyarakat (JPPM), 2025)
This community service activity aimed to enhance the capacity of educators at similar early childhood education units Aster 131 Jember in applying sensory integration stimulation through a multisensory approach—specifically, brain gym activities accompanied by regional songs. The program was initiated in response to the diverse developmental conditions of the students and the teachers’ limited access to media for introducing art and local culture. Therefore, an innovative learning strategy was needed to support both inclusive education and cultural introduction. The activity was carried out in five stages: initial survey, awareness-raising session, training of trainers (ToT), implementation of pre-learning activities with students, monitoring, and post-intervention evaluation. Data were collected through pre- and post-tests for teachers and a satisfaction survey administered after the program. The results indicated an increase in teachers’ understanding of the importance of sensory integration in early childhood, improvement in their skills in implementing brain gym activities, and active student participation in pre-learning sessions that combined motor skills and local cultural elements. The satisfaction survey showed that teachers found this method enjoyable, easy to apply, and relevant to children's needs. This initiative recommends the implementation of culturally grounded multisensory approaches as an effective strategy to support inclusive and high-quality early childhood education.